CTA-Based Truncal-Type Occlusion Is Best Matched With Postprocedural Fixed Focal Stenosis in Vertebrobasilar Occlusions - Lee, Seong-Joon; Hong, Ji Man; Choi, Jin Wook; Kang, Dong-Hun; Kim, Yong-Won; Kim, Yong-Sun; Hong, Jeong-Ho; Yoo, Joonsang; Kim, Chang-Hyun; Sohn, Sung-Il; Hwang, Yang-Ha; Lee, Jin Soo (Frontiers in Neurology, 2019)
Background: Differentiation of embolic and atherosclerotic occlusions is difficult prior to endovascular treatment (EVT) of acute ischemic stroke due to intracranial large artery occlusions. CTA-determined occlusion type has been reported to be associated with a negative cardiac embolic source and stent retriever failure, a potential of intracranial atherosclerosis (ICAS)-related occlusions. In this study, we evaluated the agreement between preprocedural identification of CTA-determined truncal-type occlusion (TTO) and postprocedural evaluation of underlying fixed focal stenosis (FFS) in the occlusion site. Methods: Patients who underwent intracranial EVT for acute ischemic stroke within 24 h of onset and who had baseline CTA were identified from a multicenter registry collected between January 2011 and May 2016. Preprocedural occlusion type was classified as TTO (target artery bifurcation saved) or branching-site occlusion (bifurcation involved) on CTA. As for postprocedural identification, FFS was evaluated by stepwise analyses of procedural and postprocedural angiographies. The agreement between TTO and FFS was evaluated in respective intracranial vascular beds. Receiver operating characteristics analyses were also performed. Results: A total of 509 patients were included [intracranial internal carotid artery (ICA): 193, middle cerebral artery (MCA) M1: 256, and vertebrobasilar artery (VBA): 60]. In preprocedural identification, 33 (17.1%), 41 (16.0%), and 29 patients (48.3%) had TTOs, respectively. TTOs had good agreement with angiographic FFS in M1 (positive predictive value: 63.4%, negative predictive value: 83.2%, likelihood ratio: 5.42, Pmultivariate < 0.001) and VBA (72.4%, 96.8%, and 4.54, respectively, Pmultivariate = 0.004), but not in intracranial ICA occlusions (Pmultivariate = 0.358). The area under the receiver operating characteristics curve was the largest for VBA (0.872, p < 0.001), followed by MCA M1 (0.671, p < 0.001), and intracranial ICA (0.551, p = 0.465). Conclusions: Agreement between preprocedural TTO and postprocedural FFS, both of which are surrogate markers for ICAS-related occlusions, is highest for VBA, followed by MCA M1 occlusions. There is no significant association in intracranial ICA.